Electrochemical stability on 1-ethyl-3-methylimidazolium bis (trifluoromethyl sulfonyl) imide ionic liquid for dye sensitized solar cell application - Lohmoh, M.-A. (Elsevier B.V., 2020)
The usage of ionic liquids has recently became a promosing alternative for replacement of conventional volatile organic-based electrolyte for Dye Sensitized Solar Cells (DSSCs) due to its electrochemical stability, high conductivity and low vapor pressure. However, degradation of ionic liquid concentration is one of the major concerns which affect the efficiency of DSSCs. By using electro-oxidation method, this research aimed to evaluate the degradation of 1-Ethyl-3-Methylimidazolium bis (trifluoromethyl sulfonyl) imide EMIMN(Tf)2 ionic liquid by analyzing the change of concentration with respect to high voltage differences (i.e., 1 V, 2 V, 4 V, 6 V, 8 V and 10 V). FT-IR result shows that there is slight degradation in the concentration amount of EMIMN(Tf)2 ionic liquid which is almost negligible and there is no change in spectrum as well as functional group when compared with standard curve of EMIMN(Tf)2 ionic liquid from 1 V to 10 V. Apart from that, the degradation percentage of each voltage at 60 min are 8.48%, 7.90%, 3.82%, 6.08%, 3.51% and 2.86%, respectively. The highest Iron (Fe) amount was 224.45 ppm at the condition of 6 V at 5 min. It is proven that EMIMN(Tf)2 has high capability to be used as an electrolyte as it has high electrochemical stability in the voltage range from 1 V to 10 V. Â© 2020